FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEK PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BARAMBAI - Khairiah, Khairiah; Rusmilawaty, Rusmilawaty; Hapisah, Hapisah; Suhrawardi, Suhrawardi (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Introduction: Chronic energy deficiency in pregnant women is a condition where the mother lacks protein and energy during pregnancy, which can lead to health problems for both the mother and the fetus. In 2021, 666 pregnant women (16.8%) in Barito Kuala Regency experienced Chronic Energy Deficiency (CED) (Barito Kuala Health Profile, 2022). At the Barambai Community Health Center, CED cases increased from 5.93% (2023) to 9.23% (2024).Objective: To determine the factors related to the occurrence of KEK in pregnant women in the Barambai Health Center work area.Methods: Quantitative research with case-control analytical survey design. The population includes all pregnant women registered at the Barambai Health Center in 2024, totaling 239 people. The sample size was 54 people, consisting of 18 pregnant women with KEK (cases) and 36 without KEK (controls). Secondary data were obtained from cohort documentation and analyzed using the chi-square test.Results: The results of the study showed that out of 54 samples, 36 pregnant women (66.7%) experienced CED and 18 pregnant women (33.3%) did not experience CED. 11 pregnant women with risk age (61.1%) experienced CED, while in the non-CED group, most (75%) were at a non-risk age. Risky parity was found in 12 people (66.7%) who experienced CED, while 72.2% of the non-CED group had non-risk parity. A total of 13 pregnant women (72.2%) with a risky pregnancy spacing experienced CED, while 66.7% of the non-CED group had a non-risk pregnancy spacing. The results of statistical tests showed a significant relationship between age (p = 0.022), parity (p = 0.014), and pregnancy spacing (p = 0.016) with the incidence of CED.Conclusion: There is a relationship between age, parity, and pregnancy spacing with the incidence of KEK in pregnant women in the Barambai Health Center work area.